Identificação de alunos com altas habilidades ou superdotação a partir de uma avaliação multimodal - Mendonça, Lurian Dionizio [UNESP] (2015)
Intelligence has always been a mystery and a challenge for many companies, even more, when people have higher intelligence to the average population. Brazilian law, to rely on the National Policy for Special Education in the Perspective of Inclusive Education, puts students with high ability or giftedness (AH/SD) as target of Special Education, that is, with the right to have an educational service specialized because it is people who may require different teaching and learning programs. However, before these students receive a call, it is essential to be identified, as this is the first step to meet their special educational needs, whatever they may be. So, in this study raised the hypothesis that a multimodal review, including, in addition to assessments of intellectual and academic performance of students, the child's developmental history, plus an instrument that aims to identify the area of giftedness of student, can support decision-making for referral to a specialized care service, enabling the full development of the potential of this population. In order to achieve the proposed objectives, this study was divided into four articles, the first of which seeks to identify students with AH/SD through an initial screening using tests to evaluate the intellectual and academic performance (Test of Progresive Matrices and School Performance Test - TDE), beyond the suggestion of teachers (List of items to note in the classroom). The second article, aims to conduct a confirmatory evaluation with the WISC-III, the students identified in the initial screening. The third study, aimed to describe the profile of these identified students in the confirmatory evaluation, including the following instruments, Scales for Rating the Behavioral Characteristics of Superior Students - Revised Edition - SRBCSS-R (repond teachers), the Features Checklist of Characteristics Associated with Giftedness - CCAS (parents respond) and also the grades obtained by...